2017
DOI: 10.1128/jvi.00754-17
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Salts Block Hepatitis E Virus Replication by Inhibiting the Activity of Viral RNA-Dependent RNA Polymerase

Abstract: Hepatitis E virus (HEV) causes an acute, self-limiting hepatitis in healthy individuals and leads to chronic disease in immunocompromised individuals. HEV infection in pregnant women results in a more severe outcome, with the mortality rate going up to 30%. Though the virus usually causes sporadic infection, epidemics have been reported in developing and resource-starved countries. No specific antiviral exists against HEV. A combination of interferon and ribavirin therapy has been used to control the disease w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
123
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 41 publications
2
123
1
4
Order By: Relevance
“…Zinc salts have been shown to inhibit some of the RNA viruses using in vitro assays or infection systems (4)(5)(6)(7)(8)(9). Zinc has been shown to alter various stages of viral infection as in the case of poliovirus and other picornaviruses and hepatitis C virus where zinc salts were shown to inhibit viral protease activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc salts have been shown to inhibit some of the RNA viruses using in vitro assays or infection systems (4)(5)(6)(7)(8)(9). Zinc has been shown to alter various stages of viral infection as in the case of poliovirus and other picornaviruses and hepatitis C virus where zinc salts were shown to inhibit viral protease activity (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have also shown divergent effects of Zn 2+ on virus replication. Zinc inhibited RNA polymerase activity of a number of viruses including coronavirus, arterivirus, rhinovirus, and hepatitis C virus (4)(5)(6)(7)(8)(9). Dengue virus (DENV), a mosquitoborne, positive-strand RNA virus from the family Flaviviridae, has emerged as one of the major public health concerns in India and recent estimates suggest that over 60 million people globally get infected with DENV every year (10).…”
Section: Introductionmentioning
confidence: 99%
“…63,64 Zinc salts were shown to block the replication of both genotype 1 and genotype 3 HEV by inhibiting the activity of viral RNA-dependent RNA polymerase in cultured human hepatoma cells. 62 Further, zinc salts did not affect virus entry into the host cell. Zinc also displayed moderate cooperativity with ribavirin in inhibiting viral replication.…”
Section: Carbobenzyl-leu-leu-leu-aldehyde (Mg132)mentioning
confidence: 93%
“…6 | 310-316 MG132 also reduced the cellular RNA and protein levels, indicating its effect to be nonspecific. 61 Zinc A recent report by Kaushik et al 62 has demonstrated the antiviral activity of zinc against HEV. Zinc is an essential micronutrient, which plays a crucial role in multiple cellular processes.…”
Section: Carbobenzyl-leu-leu-leu-aldehyde (Mg132)mentioning
confidence: 99%
“…2 Recently, zinc salt, which is known to reduce infections induced by viruses, was tested in vitro against HEV. 3,4 It has been shown that it inhibits the activity of viral RNA-dependent RNA polymerase (RdRp), leading to inhibition of HEV replication. 3,4 In addition, it has a synergistic effect with ribavirin on HEV replication.…”
Section: Failure To Respond To Ribavirin Despite Elevated Intra-erythmentioning
confidence: 99%